Conrad and impressionism - Peters, John G. (John Gerard) (Cambridge University Press, 2001)
John Peters investigates the impact of Impressionism on Conrad and links this to his literary techniques as well as his philosophical and political views. He investigates the sources and implications of Conrad's impressionism in order to argue for a consistent link between his literary technique, philosophical presuppositions and socio-political views.